Contact Dermatitis - Johansen, Jeanne Duus.; Frosch, Peter J.; Lepoittevin, Jean-Pierre.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
The fifth edition of Contact Dermatitis covers in detail every conceivable aspect of irritant and allergic contact dermatitis and its modern-day management. Special emphasis is given to immunological mechanisms, molecular aspects of sensitizers, atypical clinical forms, reactions to medicaments, and occupational and environmental factors. In order to optimize the diagnostic approach, a wide range of information is provided, including a dictionary of contact allergens. Retained chapters from the previous edition have been thoroughly revised to reflect the latest knowledge. Furthermore, completely new chapters have been added on a variety of topics, including genetics, the role of the skin barrier, the link between respiratory symptoms triggered by chemicals and contact dermatitis, and prevention. The editors and authors are all leading practitioners in the field. The comprehensive but approachable text is supplemented by a large number of full color illustrations and tables. Core messages highlight the most important information and will help the reader to gain a better understanding of the subject and greater competence in everyday practice.
Basic Features -- Pathology -- Dermatotoxicology -- Clinical Features -- Diagnostic Tests -- Allergic Contact Dermatitis Related to Specific Exposures -- Therapy, Rehabilitation and Prevention.
Keywords: Medicine; Allergy; Dermatology; Medicine, Industrial; Medicine & Public Health; Dermatology; Allergology; Occupational Medicine/Industrial Medicine